Enforcing constitutional conventions. (21st January 2020) - Ahmed, Farrah; Albert, Richard; Perry, Adam
Abstract: In an earlier article, we disproved the three claims central to the dominant view in the study of constitutional conventions: that there is a shared "Commonwealth approach" to constitutional conventions; that Commonwealth courts will recognize and employ conventions but never enforce them; and that conventions are sharply distinguishable from rules of law. We drew from Canada, India, and the United Kingdom to demonstrate that Commonwealth courts have recognized, employed, and indeed also enforced conventions. In this article, we turn from the descriptive to the normative, arguing, again in contrast with the dominant view, that Commonwealth courts sometimes should enforce conventions. We argue that courts should act as executors of the will and judgment of constitutional actors, and limit themselves to enforcing only power-shifting conventions: conventions which transfer power from those who have legal power to those who can legitimately wield it. In playing this role, judges uphold the legitimate allocation of power—legitimate, not according to judges but according to constitutional actors themselves.